El Séfer Méšec betí, de Eliézer Papo : ritos y costumbres sabáticas de los sefardíes de Bosnia - Šmid, Katja (Publicaciones de estudios sefardíes ;, 2012)
This book presents for the first time the complete text of Séfer Mésec betí, a work by Rabbi Eliezer Papo, that deals with the laws of Sabbath from the Sephardic/Bosnian perspective. Papo gives a lot of attention to Gentiles in relation to the Sabbath. This work was first published in Sarajevo (Bosnia) in 1871. Included in this work are an introduction, commentary, glossary and bibliography written by Katja Smid.